Efektivitas Undang-undang Pajak Daerah dan Retribusi Daerah dalam Peningkatan Penerimaan Pajak Daerah Kabupaten / Kota di Wilayah Sumatra - Batara Daniel Bagana; Maryono, Maryono; Bambang Sutedjo (Politeknik Ganesha Medan, 2024)
This study aims to analyze the effectiveness of Law Number 28 of 2009 concerning regional taxes and regional levies in increasing district/city tax revenues in Sumatra. The problem that occurs today is still a very low level of financial independence of districts/cities as measured by the contribution of local original income to regional income on average is below 25 percent. The population in this study includes districts and cities in Sumatra. The total number consists of 121 districts and 32 cities with observation years for two years from 2019 to 2020. The results showed that local tax revenues from all new types of local taxes consisted of rural and urban land and building taxes, duties on the acquisition of land and building rights, groundwater taxes, and swallow's nest taxes in regencies and cities in Sumatra on average in 2019 amounted to Rp. 28,573,177,419, - and in 2020 amounted to Rp. 27,649,013,349, - and its contribution to regional tax revenue was also quite large, namely in 2019 by 27 percent and in 2020 by 31 percent. The sizable contribution of regional tax revenue from the new type of regional tax contained in Law number 28 of 2009 concerning regional taxes and regional levies encourages increasing the financial capacity of districts/cities in Sumatra and increases the harmonization of government financial capacity vertically, namely the central government. , provincial government, and district/city government. Thus, it can be concluded that law number 28 of 2009 concerning regional taxes and regional levies is effective in increasing regional tax revenues in districts and cities in Sumatra, thereby increasing the financial capacity of districts and cities in Sumatra.